Analysis of sex differences in cancer-specific survival and perioperative mortality following radical cystectomy: results of a large german multicenter study of nearly 2500 patients with urothelial carcinoma of the bladder - Otto, Wolfgang; Trojan, Lutz; Höfner, Thomas; Hohenfellner, Markus; Haferkamp, Axel; Müller, Stefan C.; Kocot, Arkadius; Riedmiller, Hubertus; Wieland, W.; Stief, Christian Georg; Bastian, Patrick J.; Burger, Maximilian (Gender medicine, 2012)
Background Outcome of patients with urothelial carcinoma of the bladder (UCB) varies between sexes. Although overall incidence is higher in men, cancer-specific survival (CSS) has been suggested to be lower in women. Although the former effect is attributed to greater exposure to carcinogens in men, the latter has not been elucidated.Objectives The aim of the study was to identify sex-specific outcomes based on one of the largest databases of patients with UCB who underwent radical cystectomy (RC). Methods This retrospective multicenter series comprised 2483 patients in Stage M0 who underwent RC for UCB from 1989 to 2008; 20.4% of patients were women. The impact of sex on CSS in the entire study group and in specific subgroups was analyzed. The median follow-up time was 42 months (interquartile range, 21-79). Results Histopathologic criteria of pathologic tumor (pT), pathologic nodal (pN), grade, lymphovascular invasion (LVI), and associated carcinoma in situ (CIS) of the study did not differ between sexes. The percentage of female patients increased over time. Five-year CSS in female patients was significantly lower than in male patients (60% vs 66%; P = 0.005). In multivariate analysis adjusted to other covariates, tumor stage ≥pT3 (hazard ratio [HR] = 2.44; P < 0.001), positive pN status (HR = 1.91; P < 0.001), LVI (HR = 1.48; P < 0.001), lower count of lymph nodes removed (HR = 0.98; P = 0.002), older age (HR = 1.01; P < 0.001), and female gender (HR = 1.26; P = 0.011) had an independent impact on CSS. Deterioration of CSS in female patients was pronounced when LVI was present (HR = 1.57; P < 0.001) and when RC was performed in the earlier time period (HR = 2.44; P < 0.001). However, women showed significantly lower perioperative mortality (within 90 days after RC) compared with men. Conclusions After RC for UCB, cancer-specific mortality was higher in female patients; this disadvantage was more pronounced in earlier time periods. In addition, worse outcome of women with verified LVI was shown to be comparable with men. These findings were suggestive of different tumor biology and potentially unequal access to timely RC in earlier time periods because of reduced awareness of UCB in women. Further studies are required to improve UCB outcome in both sexes, notably in female patients.
Gesehen am 24.04.2018